Density distribution of Penaeus merguensis De Man, 1888 based on habitat in the waters of Merauke District, South Papua Province, Indonesia - BONNY LANTANG; NAJAMUDDIN NAJAMUDDIN; ALFA FILEP PETRUS NELWAN; MUHAMMAD FARID SAMAWI (Society for Indonesian Biodiversity, 2023)
Abstract. Lantang B, Najamuddin, Nelwan AFP, Samawi MF. 2023. Density distribution of Penaeus merguensis De Man, 1888 based on habitat in the waters of Merauke District, South Papua Province, Indonesia. Biodiversitas 24: 4427-4437. The waters of Merauke District, located in the Arafura Sea area, have relatively hight penaeid resource, but prawn fishing productivity is the lowest of 11th other Indonesian fisheries management areas.. The optimization of the fishery resource utilization remains poor after the moratorium on fishing vessel licensing in 2014, which is only 11%. Hence, a study is needed to determine the resources’ distribution, abundance, and sustainability. This research aims to analyze the density distribution of banana prawn (Penaeus merguensis De Man, 1888) based on the habitat type, each location separated by 4-5 kilometers within the coastal ecosystem waters of Merauke District. The research was carried out from March to August 2022. Data were collected within each habitat: the catch, prawn fishing equipment, and oceanographic parameters, and then analyses were undertaken using statistical tests. The results showed that the highest density of banana prawn was obtained in shallow waters adjacent to the mangrove habitat at Bokem (32.68 kg/km2) and Yobar (20.27 kg/km2). In waters adjacent to the sandy beach at Payum (17.98 kg/km2), the density was higher than within the estuarine habitat of Maro River (14.60 kg/km2) and adjacent to the sandy beach at Lampu Satu (14.39 kg/km2). This is due to the influx of fresh water in estuarial habitat, sandy beaches in Lampu Satu and Payum, and mangroves in Yobar, resulting in prawn emigration to areas with higher salinity in Bokem mangroves. It is also thought to be associated with increasing turbidity with a similar pattern in salinity and affecting the density of banana prawns.